2020
DOI: 10.1242/jcs.239186
|View full text |Cite
|
Sign up to set email alerts
|

FAK regulates actin polymerization during sperm capacitation via the ERK2/GEF-H1/RhoA signaling pathway

Abstract: Actin polymerization is a crucial process during capacitation. We have recently described the participation of FAK in actin polymerization in guinea pig spermatozoa. However, the mechanism by which FAK achieves these processes is unknown. Our data showed that ERK2 is activated during the first minutes of capacitation; its inhibition blocked actin polymerization and the acrosome reaction. Additionally, the present study found that FAK is involved in ERK2 activation since FAK was phosphorylated in Tyr925 and bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 90 publications
3
7
0
Order By: Relevance
“…Additionally, our recent publication showed that ex vivo manipulation of stress signaling in spermatozoa changed transcriptional profiles of 84% mitochondrial dynamics/functionality markers and that most of these effects are mediated through α1-and/or-β-adrenergic receptors [ 14 ], which are very well known activators of ADCY-cAMP-PRKA-signaling [ 15 ]. In relation to MAPK signaling, our results are showing increased transcription of 80% of MAPKs, and they could be compared with findings that testicular hyperthermia induces both MAPK1/3 and MAPK14 [ 68 ] and that MEK1/2 and ERK2 regulate actin polymerization associated with spermatozoa capacitation [ 69 ].…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, our recent publication showed that ex vivo manipulation of stress signaling in spermatozoa changed transcriptional profiles of 84% mitochondrial dynamics/functionality markers and that most of these effects are mediated through α1-and/or-β-adrenergic receptors [ 14 ], which are very well known activators of ADCY-cAMP-PRKA-signaling [ 15 ]. In relation to MAPK signaling, our results are showing increased transcription of 80% of MAPKs, and they could be compared with findings that testicular hyperthermia induces both MAPK1/3 and MAPK14 [ 68 ] and that MEK1/2 and ERK2 regulate actin polymerization associated with spermatozoa capacitation [ 69 ].…”
Section: Discussionsupporting
confidence: 58%
“…In the present work, we observed an increase in F-actin levels in capacitated cryopreserved bull sperm after 15 min capacitation, and a decrease in polymerized actin 30 min later. Similar actin polymerization dynamics displaying a peak has been described in other species such as guinea pig 55 .…”
Section: Discussionsupporting
confidence: 78%
“…Paxillin is a multi-domain adaptor between the plasma membrane and the actin cytoskeleton [ 59 ] that serves as a docking protein for recruiting signaling molecules [ 60 ]. FAK is a cytoplasmic tyrosine kinase that localizes to FAs and regulates actin cytoskeleton remodeling for integrin-mediated processes such as cell spreading and migration [ 61 ], for example, by participating in actin polymerization [ 62 , 63 ]. The ‘force transduction layer’ contains mechanosensitive proteins such as talin and vinculin [ 64 , 65 ], which play key roles in mechanotransduction, as recent evidence suggests that talin is the key force-sensing molecule and vinculin one of the key mechanoeffectors [ 66 ].…”
Section: Proteins and Structures Involved In Stiffness Sensingmentioning
confidence: 99%